PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP KINERJA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Muhammad Rosidi; Achad Noerasmawati (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2022)
The purpose of the original research is related to and analyze the consequences of the company's social responsibility. Head Tide Sindh By 2013 in Punjab, and in 2013, the number includes the number after 2013. 175-2011. The sample has been obtained on a model that has been added in the country in the country, in the country, the 48 registered manufacturers in 144 data. The analysis of data and adhesives of data analysis in this study is used. The results of this study as difficult effects of severe effects, social responsibility of social influences and the company's social responsibility